2023
DOI: 10.1038/s41598-023-37843-1
|View full text |Cite
|
Sign up to set email alerts
|

The impact of bilateral anodal transcranial direct current stimulation of the premotor and cerebellar cortices on physiological and performance parameters of gymnastic athletes: a randomized, cross-over, sham-controlled study

Abstract: Professional sports performance relies critically on the interaction between the brain and muscles during movement. Transcranial direct current stimulation (tDCS) is a noninvasive brain stimulation technique which modulates cortical excitability and can be used to improve motor performance in athletes. The present study aimed to investigate the effect of bilateral anodal tDCS (2 mA, 20 min) over the premotor cortex or cerebellum on motor and physiological functions and peak performance of professional gymnasti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 81 publications
0
3
1
Order By: Relevance
“…The findings of the current study are not consistent with the findings of the majority of the initial previous single-session c-tDCS studies by other research groups [6][7][8][9][10], although most of these studies used adaptation-learning paradigms. Furthermore, the findings differ from a very recent study that reported that c-tDCS improved strength and coordination in full-body motor tasks in gymnasts [55]. However, this study used a novel bilateral electrode montage.…”
Section: Effects Of C-tdcs On Motor Learningcontrasting
confidence: 82%
See 1 more Smart Citation
“…The findings of the current study are not consistent with the findings of the majority of the initial previous single-session c-tDCS studies by other research groups [6][7][8][9][10], although most of these studies used adaptation-learning paradigms. Furthermore, the findings differ from a very recent study that reported that c-tDCS improved strength and coordination in full-body motor tasks in gymnasts [55]. However, this study used a novel bilateral electrode montage.…”
Section: Effects Of C-tdcs On Motor Learningcontrasting
confidence: 82%
“…Nonetheless, it is possible that another set of c-tDCS parameters could be more effective. For example, a recent study used bilateral anodal c-tDCS and demonstrated improvements in complex whole-body tasks in gymnasts [55]. Another study found that a bilateral electrode montage (anode over the right cerebellar hemisphere, cathode over the left cerebellar hemisphere) and a 4 mA current strength outperformed several other unilateral montage and lowercurrent-strength combinations.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…With the exception of eight studies applying a cephalic montage of the return electrode, all examined studies applied an extracephalic montage of the return electrode. Regarding the tDCS application protocol, all studies opted for the offline modality (testing after stimulation), with five studies including also the online stimulation modality (testing during stimulation) ( Hazime et al, 2017 ; Vargas et al, 2018 ; Fortes et al, 2022 ; Moreira et al, 2022 ; Anoushiravani et al, 2023 ). Three studies out of 18 studies did not measure side effects of the tDCS intervention.…”
Section: Resultsmentioning
confidence: 99%
“…Critically, the authors used a multi-modal stimulation protocol, where activity of the dorsolateral prefrontal cortex (dlPFC) was additionally suppressed. In another study, trained gymnasts were investigated to evaluate the effects of bilateral anodal CB-tDCS on static and dynamic strength performance [ 61 ]. Again, no performance improvements were observed for static and dynamic strength in the study.…”
Section: Discussionmentioning
confidence: 99%